2019
DOI: 10.1016/j.scitotenv.2018.11.190
|View full text |Cite
|
Sign up to set email alerts
|

The associations between lead exposure at multiple sensitive life periods and dental caries risks in permanent teeth

Abstract: Background: Dental caries is an important public health problem in Mexico, a country also faced with high exposure to toxicants including lead (Pb). Methods: Participants were 386 children living in Mexico City. Prenatal (trimester 1-3), earlychildhood (12, 24, 36, and 48 months of age) and peri-pubertal (10-18 years of age) blood Pb levels were quantified using graphite-furnace atomic-absorption spectroscopy. Maternal patella and tibia bone Pb at 1 month postpartum were quantified with K X-ray fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The present evidence shows that dental caries, when including enamel caries, could be very prevalent with a prevalence rate of over 80% among most populations aged 12-15 years, as was our population (55)(56)(57). The reason for a high prevalence rate could be insufficient awareness of initial caries in most adolescents, their guardians and even clinical dentists.…”
Section: Discussionmentioning
confidence: 47%
“…The present evidence shows that dental caries, when including enamel caries, could be very prevalent with a prevalence rate of over 80% among most populations aged 12-15 years, as was our population (55)(56)(57). The reason for a high prevalence rate could be insufficient awareness of initial caries in most adolescents, their guardians and even clinical dentists.…”
Section: Discussionmentioning
confidence: 47%
“…Details of the cohort have been reported elsewhere [Perng et al, 2019]. During 2015-2016, a sample of 550 children and adolescents were assessed in the ABC Hospital research center as a part of a dental study [Wu et al, 2019]. We excluded from this analysis participants younger than 12 years who had mostly primary teeth, as well as participants who refused the oral examination, resulting in a final analytical sample of 402 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis has been conducted regarding this population's prenatal exposure to lead and will be reported in another publication. 11 ICDAS development and approach to caries detection and assessment has been explained in detail elsewhere. 21 Each carious lesion was classified based on depth of the lesion within the tooth.…”
Section: Methodsmentioning
confidence: 99%
“…10 However, in 2004, Gomes et al also found no link between lead concentrations and DMF count of 329 preschool children. 11 Both Youravong et al in 2006 and Ceni c-Milosevi c et al in 2013 found positive associations with lead exposure and high DMF counts. 12,13 There are several hypotheses as to how lead may affect dental caries.…”
Section: Introductionmentioning
confidence: 95%